Influence of Rice Husk Ash and Fly Ash on Properties of Red Clay (Journal of Scientific Research, 2014)
Effects of rice husk ash and fly ash on properties of red clay collected from Naogaon district of Bangladesh were investigated. Different percentages of rice husk ash (RHA) and fly ash (5%, 10% and 15%) were thoroughly mixed with clay to analyse various physical and chemical properties of clay followed by heat treatment of 8000C to 11000C. The samples were tested for compressive strength, linear shrinkage, water absorption, porosity and bulk density. XRD analysis indicates the clay sample was mainly illite type. Water absorption and porosity increased with increasing percentage of ashes. The percentage of water absorption was within 6 to 10% for different mixture which may be suitable for ceramic and tiles purposes. Both fly ash and RHA of 15% could be used to improve some properties of clay. The optimum firing temperature for all the samples was 10500C. XRD pattern of clay with fly ash and rice husk ash heated at 10500C confirms the presence of feldspar and quartz as major phase and hematite (Fe2O3) and cristobalite phase as minor phase. This red clay deposits reinforced with different appropriate quantities of rice husk ash and fly ash could be used for various low temperature applications in industry and construction purposes. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i3.15343 J. Sci. Res. 6 (3), 421-430 (2014)